Evaluating the Feasibility and Effectiveness of a Measurement Device to Be Used Intraoperatively During Aortic Valve Repair - Qureshi, Rohail (Université d'Ottawa / University of Ottawa, 2021)
The ability to accurately and in a repeatable fashion, measure aortic valve dimensions during aortic valve repair is critical to the restoration of function in a diseased aortic valve, as for example in aortic insufficiency. Although several methods for measuring aortic valve dimensions have been shown to be feasible, they are approximate and lack the accuracy, robustness, and repeatability one would expect to support aortic valve repair surgery. In addition, they do not allow for the intra-operative measurement of aortic valves under conditions equivalent to the physiological (pressurized) state. A prototype medical device was designed, and 3-D printed at the University of Ottawa that would allow cardiac surgeons performing aortic valve repair to do just that. The prototype was tested for its accuracy and precision at the University of Ottawa Heart Institute using porcine aortic valves. Based on unsatisfactory results of this experimentation, namely, that the device was applying forces that were too large, a numerical simulation study was designed using a commercial finite element software LS-DYNA. This simulation study was used to explore the forces that the prototype device needed to apply to obtain end-diastolic pressurized dimensions of the aortic valve. The simulation study showed that one single device was likely not possible to obtain measurements in an aortic valve. However, a system of two devices could be imagined, one to measure the STJ diameter and free margin length of the aortic valve cusps, and one to measure the cusp height of the same valve, for the purposes of aortic valve repair.
Keywords: Aortic valve repair; Aortic valve dimensions; Measurement device for aortic valve